Changes of Material Properties of Silumin During Age-Hardening - Jan Kohout (Communications - Scientific letters of the University of Zilina, 2012)
Simple phenomenological description of age-hardening kinetics of supersaturated solid solution is presented using the sum of exponential functions with negative arguments containing rate constants whose temperature dependence is described by the Arrhenius equation. To determine the number of exponentials in the sum is very important: it should be sufficiently high to obtain accurate description of kinetics and sufficiently low to keep the simplicity and practical applicability of this description. The HB hardness and growth changes (i.e. relative length increase) of silumin during age-hardening are studied separately and then commonly as various manifestations of the same hardening.